IN-SITU WETTABILITY DETERMINATION: A CASE STUDY OF CARBONATE RESERVOIR - IZZA WIHDANY, FALZA
Rock wettability is a property affecting capillary pressure, relative permeability, electrical properties, performance of water production, waterflood, and enhanced oil recovery. Wettability of a core sample is usually measured in the laboratory. But unfortunately, the process of transferring the core samples from the reservoir to the laboratory may produce changes in the wettability properties (especially during core cutting operation and sample preparation). In addition, the wettability change may occur as a result of fluid samples which were used for testing in the laboratory have different properties to the fluid in the reservoir. Therefore, this study is to point out in real that the wettability changes in core sample can occure and need to be evaluated integratedly the cause and the side effect of wettability changes for another rock properties. In-situ wettability determination in this study use the interpretation method of fluid level distribution which employs the plot between reservoir pressure and true vertical depth, and well log data especially resistivity log. Reservoir pressures are obtained from Drill Stem Test and Formation Test data. Water saturation log is calculated using Archie equation, while the value of “a”, “m”, dan “Rw” is attained from Picket Plot. Saturation expoenent, n, is determined using two methods using well log data. Then, capillary pressure curve is reconstructed using water saturation log. Relative permeability, capillary pressure, and electrical property obtained from the core measurement of TB reservoir shows that the wettability of reservoir TB is water wet. The interpretation result of in-situ wettability using reservoir pressure test data suggests that the wettability of rock is intermediate or weakly oil wet. This study also shows the capillary pressure which is more representative than the capillary pressure data from laboratory test. Furthermore, this study gives us awareness that it is important to pay attention to things that can alter the wettability from original condition.